Exploring the relationship of social networks on team effectiveness: a cross-cultural study of collegiate student-athletes in Korea and Hong Kong - Kim, Seungmo; Park, Sanghyun; Love, Adam (Frontiers in Sports and Active Living, 2025)
The purpose of the current study was to explore the relationship between college sports teams’ social networks (i.e., cohesion) and performance (i.e., effectiveness) within distinct sports cultures—specifically, elite sports in Korea vs. recreational sports in Hong Kong. A total of 600 student-athletes participated in a survey, comprising 256 athletes from 30 teams (12 men's teams and 18 women's teams) in Korea and 344 athletes from 27 teams (14 men's teams and 13 women's teams) in Hong Kong. Based on their response regarding advice network among teammates, total 57 Teams were categorized into dense (high advice network density) and sparse (low advice network density) based on median advice density values (S. Korea: 0.388, Hongkong: 0.431), resulting in four groups: 1. dense advice network in Hong Kong, 2. sparse advice network in Hong Kong, 3. dense advice network in Korea, and 4. sparse advice network in Korea. An ANCOVA analysis was conducted on the sub-dimensions of team effectiveness (i.e., effort, ability, preparation, persistence, and unity) to compare means across these groups. The study found that teams in Korea demonstrated greater effectiveness in terms of effort, ability, and preparation compared to those in Hong Kong. Interaction effect between network and nationality affected effort and utility of team effectiveness, and overall, Korea's dense network group outperformed Hong Kong's network group in terms of team effectiveness.